Frequency and effects of seasonal flu vaccines on exacerbations of chronic obstructive pulmonary disease in Serbia - Ilić, Miroslav; Kopitović, Ivan; Vulin, Aleksandra; Zvezdin, Biljana; Hromiš, Sanja; Kolarov, Violeta; Kuhajda, Danijela; Vukoja, Marija (Vojnosanitetski pregled, 2021)
Background/Aim. The influenza virus is often the cause of exacerbations among chronic obstructive pulmonary disease (COPD) patients, especially during the winter season. However, vaccination rates are still below recommended even in developed countries. The aim of the study was to determine the rates and examine the effectiveness of immunization against seasonal influenza in preventing exacerbations among COPD patients in Serbia. Methods. The prospective cohort study of stable COPD outpatients was conducted over three years (between October 1, 2014, and September 30, 2017) at the Polyclinic Department of Institute for Pulmonary Diseases of Vojvodina, Sremska Kamenica, Serbia. The rates and effects of seasonal flu vaccination on COPD exacerbation rates were evaluated using univariate and multivariate logistic regression analysis, taking into account comorbidity, age, and body mass index (BMI). Results. The study included 840 patients. The flu vaccination rate was 37.1%. Exacerbations occurred more frequently in unvaccinated patients [176 (31.9%) vs. 375 (68.1%), p = 0.043]. In elderly vaccinated patients (≥ 65 years) there were fewer exacerbations compared to unvaccinated patients [89 (56.0%) vs. 188 (69.4%), p = 0.005]. Lower frequency of exacerbations was also observed in vaccinated patients with comorbidities [165 (61.1%) vs. 327 (69.4%), p = 0.021] and low BMI [27 (64.3%) vs. 78 (83.9%), p = 0.011]. Multivariate logistic regression analysis identified BMI < 21 kg/m2 [relative risk (RR): 0.490; 95% confidence interval (CI): 0.318–0.758; p = 0.001] and heart failure (RR: 2.734; 95% CI: 1.121–6.669; p = 0.027) as independent predictors of COPD exacerbations. Conclusion. Immunization for seasonal influenza in Serbia is below recommended rates. Flu vaccination was associated with a significant reduction in COPD exacerbation rates, particularly in elderly patients and patients with heart failure and low BMI.